A new core–shell magnetic mesoporous surface molecularly imprinted composite and its application as an MSPE sorbent for determination of phthalate esters. Issue 12 (2nd March 2022) - Liu, Yuxin; Song, Wei; Zhou, Dianbing; Han, Fang; Gong, Xiaoming; Pan, Pan
Abstract : A new core–shell magnetic mesoporous surface molecularly imprinted polymer (Fe3O4@SiO2@mSiO2-MIPs) which has specific adsorption for phthalate esters was synthesized by a facile and convenient method. Abstract : In this study, a new core–shell magnetic mesoporous surface molecularly imprinted polymer (Fe3 O4 @SiO2 @mSiO2 -MIPs) which has specific adsorption and rapid adsorption rate for phthalate esters (PAEs) was prepared by a convenient method. Based on this composite as a magnetic solid phase extraction (MSPE) material, a rapid, efficient and sensitive matrix dispersion magnetic solid-phase extraction gas chromatography-mass spectrometry method (DMSPE-GC/MS) was developed for the determination of PAEs in multiple liquid samples. It is the first time that Fe3 O4 @SiO2 @mSiO2 -MIPs have been prepared by bonding amino groups on the surface of a double layer silicon substrate with diisononyl phthalate (DINP) as virtual template and 3-(2-aminoethyl)-aminopropyl trimethoxymethylsilane (TSD) as functional monomer. FT-IR, TEM, EDS, SEM, XRD, BET and VSM were used to characterize the composite. The adsorption isotherm and kinetics of Fe3 O4 @SiO2 @mSiO2 -MIPs showed that it possessed fast adsorption rates (approximately 5 min to reach equilibrium), high adsorption capacities (523.9 mg g −1 ) and good recognition of PAEs. The real samples were preconcentrated by Fe3 O4 @SiO2 @mSiO2 -MIPs, under the optimum DMSPE-GC/MS conditions. Validation experiments showed that the method presented good linearity ( R 2 > 0.9971), satisfactory precision (RSD < 5.7%) and high recovery (92.1–105.8%), and the limits of detection ranged from 1.17 ng L −1 to 3.03 ng L −1 . The results indicated that the novel method had good sensitivity, high efficiency and wide sample application and was suitable for the determination of PAEs in liquid drink samples such as water, alcohol, beverages and so on.